If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2t + -5) + 2t = 5t Reorder the terms: -3(-5 + 2t) + 2t = 5t (-5 * -3 + 2t * -3) + 2t = 5t (15 + -6t) + 2t = 5t Combine like terms: -6t + 2t = -4t 15 + -4t = 5t Solving 15 + -4t = 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 15 + -4t + -5t = 5t + -5t Combine like terms: -4t + -5t = -9t 15 + -9t = 5t + -5t Combine like terms: 5t + -5t = 0 15 + -9t = 0 Add '-15' to each side of the equation. 15 + -15 + -9t = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -9t = 0 + -15 -9t = 0 + -15 Combine like terms: 0 + -15 = -15 -9t = -15 Divide each side by '-9'. t = 1.666666667 Simplifying t = 1.666666667
| 10=-27+4x | | 2x^2+4ax+3x+6a=0 | | 3468666765x-558575858=68687763456789+56789 | | 2x/5=-2 | | (3-x).5+8=18 | | 2x/5 | | -84-10x=56-38x | | 2x+37=4x+1 | | 300-2x=50+5x | | X^3-52-96=0 | | y=-27+4x | | 2(2x-1)-3(x-5)=5x-3(2x-7)+8 | | y+8y=8 | | y+8y=7 | | 5x=-32.15 | | -4x+2y=0 | | -7(1-v)-5(v-3)=-7v+5v | | (2x+2y)+(x+y)=180 | | 7x^2-12x-27=0 | | 1.5lnx=0 | | 23m-8-2m-6= | | 3+3n-1=6n+2-2n | | 5(x-1)-3(x-2)=2 | | 55-5x=80-5x | | -3.5-1.25r=-13.5 | | x-6*(-1)=3 | | -3.5-1.25r=13.2 | | ln(2+x)=0 | | -3(3y+5)-5=-6(y+5)+3y | | 6x-3y=27 | | 1.5lnx-2.5lnx=0 | | 5x/7+1/14=7/28 |